Pensamiento docente del profesor de filosofía: recuperando la experiencia de los profesores para la formación (2019)
Among the many problems that can be considered around the teaching of philosophy, the philosophy teacher in secondary education has not been sufficiently recognized despite all the wealth involved in their experiences, beliefs and disciplinary knowledge, as there is a kind of divorce between initial training and subsequent professional practice, where the former does not know what happens in the daily life of secondary education. This paper aims to show, from the theoretical contributions of professional teaching knowledge, how the teaching of philosophy is conceived by the professors who teach it, according to their particularities, the conceptions they have built around philosophy, the didactic, the students, all with the purpose of contributing to the improvement of the teaching of philosophy in our educational environment. The generalities of the theory of professional teaching thought or Pedagogical Content Knowledge, PCK for its acronym in English, as well as some testimonies of professors of philosophy of secondary education, who manifest their ideas about what it means to teach philosophy, are presented and finally some conclusions and recommendations for future teachers of philosophy in their professional training.